Comparison of 0.5M gadoterate and 1.0M gadobutrol in peripheral MRA: a prospective, single-center, randomized, crossover, double-blind study - Haneder, Stefan; Attenberger, Ulrike; Schönberg, Stefan; Michaely, Henrik J. M. (Journal of magnetic resonance imaging, 2012)
Purpose: To evaluate the diagnostic efficacy of macrocyclic paramagnetic gadolinium (Gd) chelates gadoterate (0.5 mmol/mL) and gadobutrol (1.0 mmol/mL) for the diagnosis of clinically significant abdominal/lower limb arterial diseases at 3.0T. Materials and Methods: This study was conducted as a prospective, single-center, randomized, double-blind, intraindividual study comparing single dose (0.1 mmol/kg) gadoterate enhanced-MRA (magnetic resonance angiography) with gadobutrol enhanced-MRA at 3.0T for their diagnostic potential in patients with peripheral artery disease. A total of 20 patients were included in this trial. Results: Fourteen patients were eligible for the final efficacy analysis. The overall image quality (excellent/more than adequate) was better rated with gadoterate than with gadobutrol (100% vs. 78.6%, 100% vs. 92.9%, 100% vs. 85.7%, 100% vs. 85.7% for readers 1, 2, 3, 4, respectively). Diagnostic confidence was rated high/excellent in 100% (readers 1, 2, and 3) and 92.9% (reader 4) with gadoterate compared to 92.9% (readers 1 and 2) and 85.7% (readers 3 and 4) with gadobutrol. Higher signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) values were obtained for gadobutrol compared to gadoterate (26.1/23.4, P = 0.01, and 22.7/20.2, P = 0.01). For the secondary criteria, no differences between groups were reported. No adverse events were reported. Conclusion: Gadobutrol yielded significantly higher SNR/CNR while gadoterate was better rated in terms of overall image quality and diagnostic confidence (P > 0.05).